(untitled) - Tolmie, Andy (Maidenhead, 2011)
The aim of this book is to bridge the gap between introductory and more advanced 'technical' books on quantitative methods, helping the reader to progress clearly.
Keywords: Khoa học xã hội,Social sciences; Nghiên cứu,Phương pháp thống kê,Chương trình máy tính,Research,Statistical methods,Computer programs